Evaluating citizen science projects: insights from radon research - Hoedoafia, Mabel Akosua; Martell, Meritxell; Perko, Tanja (Frontiers in Environmental Science, 2024)
Citizen science projects have garnered attention for their potential to engage the public in scientific research and address societal challenges. However, assessing their impacts has often been overlooked or approached with overly simplistic methods. Aiming to fill this gap, this article draws on existing literature to propose an evaluation framework to critically examine how citizen science initiatives influence science, society and the participants themselves. This framework is tested on four citizen sciences projects in the field of radon research through content analysis of project reports and deductive analysis of 11 semi-structured interviews with citizen scientists and coordinators of the projects. The study demonstrates the feasibility of measuring the impacts of citizen science projects across scientific, participant, societal and researcher dimensions at the outcome level but also process evaluation at the process level. Our findings indicate that the proposed framework provides a comprehensive evaluation tool for citizen science projects, particularly in the field of radon research, and underscore the significant potential for improving participants' knowledge on radon and risk mitigation strategies, as well as positive shifts in behaviour towards testing and mitigation and influencing public health policies.